1991
DOI: 10.1073/pnas.88.15.6810
|View full text |Cite
|
Sign up to set email alerts
|

Free magnesium levels in normal human brain and brain tumors: 31P chemical-shift imaging measurements at 1.5 T.

Abstract: We have studied a series of normal subjects and patients with brain tumors, by using 31p three-dimensional chemical shift imaging to obtain localized 31p spectra of the brain. A significant proportion of brain cytosolic ATP in normal brain is not complexed to Mg , as indicated by the chemical shift 6 of the f-P resonance of ATP. The ATP (3-P METHODS Imaging/31p Chemical-Shift Imaging (CSI) Spectroscopy. Combined proton imaging/31P spectroscopic examinations of patients and healthy volunteers were done on a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 29 publications
(26 reference statements)
4
56
1
Order By: Relevance
“…Therefore, free magnesium concentrations are low in most cell types. In skeletal muscle, free Mg 2ϩ has been estimated to be between 0.5 and 1.5 mmoles/kg using various methods including P-31 MRS (16,18,(30)(31)(32). In the present investigation, free Mg 2ϩ levels in the muscles of normal control subjects (mean Ϯ SEM 0.83 Ϯ 0.09 mmoles/kg for adults and 0.78 Ϯ 0.06 mmoles/kg for children) were within the reported range during rest (Tables 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, free magnesium concentrations are low in most cell types. In skeletal muscle, free Mg 2ϩ has been estimated to be between 0.5 and 1.5 mmoles/kg using various methods including P-31 MRS (16,18,(30)(31)(32). In the present investigation, free Mg 2ϩ levels in the muscles of normal control subjects (mean Ϯ SEM 0.83 Ϯ 0.09 mmoles/kg for adults and 0.78 Ϯ 0.06 mmoles/kg for children) were within the reported range during rest (Tables 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of intracellular free Mg 2ϩ and Mg-ATP have been determined with P-31 MRS in a variety of human tissues, including red blood cells, brain, liver, and muscle (14,(16)(17)(18). Magnesium deficiency has been reported in involved tissues in a number of clinical conditions, including hypertension, arteriosclerosis, cardiac arrhythmias, diabetes mellitus, and eosinophilia-myalgia syndrome (19)(20)(21).…”
Section: Conclusion Low Levels Of Mg-atp and Free Mgmentioning
confidence: 99%
“…This result is likely related to the lower ATP concentration of brain tissue (3 mM) compared to that of skeletal muscle (8 mM), ATP being the major binding site present in the cellular milieu. Nevertheless, the value found of 0.182 mM is lower than that obtained by others (Taylor et al, 1991;Halvorson et al, 1992). This is not a surprising result as the model considered in building this calibration curve contains more species that bind Mg 2+ than in all other approaches published.…”
Section: Cytosolic [Mg 2+ ] In Human Braincontrasting
confidence: 63%
“…Membrane perturb--ations that are typically associated with the neoplastic phenotype determine the release of intracellularly bound Mg. Accordingly, a seminal study showed a significant increase of intra--cellular Mg in human brain tumours by 31P--NMR (Taylor et al, 1991). Having high intracellular Mg might represent a selective advantage for the transformed cells.…”
Section: The Impact Of Extracellular Mg On Tumour Cellsmentioning
confidence: 99%
See 1 more Smart Citation